Genome-Scale Data Call for a Taxonomic Rearrangement of Geodermatophilaceae - Montero-Calasanz, Maria del Carmen; Meier-Kolthoff, Jan P.; Zhang, Dao-Feng; Yaramis, Adnan; Rohde, Manfred; Woyke, Tanja; Kyrpides, Nikos C.; Schumann, Peter; Li, Wen-Jun; Göker, Markus (Frontiers in Microbiology, 2017)
Geodermatophilaceae (order Geodermatophilales, class Actinobacteria) form a comparatively isolated family within the phylum Actinobacteria and harbour many strains adapted to extreme ecological niches and tolerant against reactive oxygen species. Clarifying the evolutionary history of Geodermatophilaceae was so far mainly hampered by the insufficient resolution of the main phylogenetic marker in use, the 16S rRNA gene. In conjunction with the taxonomic characterisation of a motile and aerobic strain, designated YIM M13156T and phylogenetically located within the family, we here carried out a phylogenetic analysis of the genome sequences now available for the type strains of Geodermatophilaceae and re-analysed the previously assembled phenotypic data. The results indicated that the largest genus, Geodermatophilus, is not monophyletic, hence the arrangement of the genera of Geodermatophilaceae must be reconsidered. Taxonomic markers such as polar lipids and fatty-acids profile, cellular features and temperature ranges are indeed heterogeneous within Geodermatophilus. In contrast to previous studies, we also address which of these features can be interpreted as apomorphies of which taxon, according to the principles of phylogenetic systematics. We thus propose a novel genus, Klenkia, with the type species Klenkia marina sp. nov. and harbouring four species formerly assigned to Geodermatophilus, G. brasiliensis, G. soli, G. taihuensis and G. terrae. Emended descriptions of all species of Geodermatophilaceae are provided for which type-strain genome sequences are publicly available. Our study again demonstrates that the principles of phylogenetic systematics can and should guide the interpretation of both genomic and phenotypic data.